2017
DOI: 10.1038/s41598-017-11185-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association study of common variants in TGFB1 and IL-6 with developmental dysplasia of the hip in Han Chinese population

Abstract: Developmental dysplasia of the hip (DDH) is a congenital or developmental deformation or misalignment of the hip joint that is affected by environmental and genetic factors. Recently, polymorphisms in both TGFB1 and IL-6 have been identified as being significantly associated with hip osteoarthritis in Caucasians. In this study, we conducted a case-control study involving 4,206 Han Chinese individuals to investigate the effects of TGFB1 and IL-6 on the disease status and severity of DDH. A total of 32 single-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The DDH is one of the most common congenital skeletal abnormalities in newborns and infants, with multiple variations in incidence rates due to different diagnostic methods and the time of diagnosis. [16,17] In the literature, it is estimated that the incidence of DDH is between 1.5 and 20/1000 newborns, being 4 to 8 times more frequent in females than males. [1821]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DDH is one of the most common congenital skeletal abnormalities in newborns and infants, with multiple variations in incidence rates due to different diagnostic methods and the time of diagnosis. [16,17] In the literature, it is estimated that the incidence of DDH is between 1.5 and 20/1000 newborns, being 4 to 8 times more frequent in females than males. [1821]…”
Section: Discussionmentioning
confidence: 99%
“…[3] This complex developmental disorder is the result of genetic and nongenetic risk factors. [6,1617] The latter factors include the female gender of the child. [2528] Regarding ultrasound examination of the right hips, in the present study we obtained for stage IA a higher frequency with statistical significance for males (90.2%), comparing with females (84.6%), with a P value of .03.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Jin et al found that GDF5 is important in the etiology of congenital dysplasia of the hip [13]. A recent study showed that TGFB1 played a genetic role in the risk of DDH [9]. All of these indicated the complex genetic components in DDH occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Several DDH susceptibility genes (e.g. GDF5, TBX4, ASPN, PAPPA2 and TGFB1) were discovered by association study in Chinese and Caucasian populations [9][10][11][12][13]. Gene mutations not only confer the sequence changes, but can also elicit certain structural change in the microenvironment [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…TGF β1-29C/T (rs1800470) is a polymorphism that has been correlated to OA among Japanese women, to hip OA among adults, to hand OA among Finnish women, and to arthritis in twenty-two case studies meta-analysis [26,[30][31][32]. While its functional role in pathogenesis remains unclear, there has been some evidence of it affecting TGF β1 secretion and function in hepatocytes [26,33]. TT genotype and T allele are the variants that have been reported to increase susceptibility to OA [24].…”
Section: Introductionmentioning
confidence: 99%